2018
DOI: 10.5194/acp-18-16363-2018
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of carbonaceous aerosols in Xi'an, China: insights from a full year of measurements of radiocarbon and the stable isotope <sup>13</sup>C

Abstract: Sources of organic carbon (OC) and elemental carbon (EC) in Xi'an, China, are investigated based on 1year radiocarbon and stable carbon isotope measurements. The radiocarbon results demonstrate that EC is dominated by fossil sources throughout the year, with a mean contribution of 83 ± 5 % (7 ± 2 µg m −3 ). The remaining 17 ± 5 % (1.5 ± 1 µg m −3 ) is attributed to biomass burning, with a higher contribution in the winter (∼ 24 %) compared to the summer (∼ 14 %). Stable carbon isotopes of EC (δ 13 C EC ) are e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 103 publications
(133 reference statements)
10
74
2
Order By: Relevance
“…F 14 C bb for EC is slightly bigger than F 14 C nf for OC because, besides biomass burning, biogenic emissions also contribute to OC but have a smaller F 14 C than that of biomass burning. The estimation of F 14 C bb and F 14 C nf has been reported in our previous study (Ni et al, 2018). Then, f bb (EC) was used to determine EC mass concentrations from nonfossil biomass (EC bb ) and fossil fuel combustion (EC fossil ):…”
Section: Estimation Of Source Contributions To Different Carbon Fractmentioning
confidence: 99%
See 3 more Smart Citations
“…F 14 C bb for EC is slightly bigger than F 14 C nf for OC because, besides biomass burning, biogenic emissions also contribute to OC but have a smaller F 14 C than that of biomass burning. The estimation of F 14 C bb and F 14 C nf has been reported in our previous study (Ni et al, 2018). Then, f bb (EC) was used to determine EC mass concentrations from nonfossil biomass (EC bb ) and fossil fuel combustion (EC fossil ):…”
Section: Estimation Of Source Contributions To Different Carbon Fractmentioning
confidence: 99%
“…The r bb , r coal and r vehicle varies with the fuel types and properties, combustion conditions, sampling and analysis methods, etc. Best estimate of r bb (4 ± 1; average ± standard deviation), r coal (2.38 ± 0.44) and r vehicle (0.85 ± 0.16) is done through a literature search and described in our earlier study (Ni et al, 2018). p is the fraction of EC from coal combustion (EC coal ) in EC fossil .…”
Section: Estimation Of Source Contributions To Different Carbon Fractmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bottom‐up technology‐based emission inventories (EIs) are acknowledged to carry an uncertainty by factors of 2–4 for BC, with the uncertainty stemming largely from variations in BC emission factors (EF, mass of BC emitted per mass fuel consumed, or product produced) but also from uncertainties in activity estimates (e.g., energy consumption data; e.g., Bond et al, ; Lu et al, ; Wang et al, ; Zhao et al, ). Observationally based studies are combining to demonstrate that the relative contributions of biomass burning versus fossil fuel combustion estimated by bottom‐up EIs are systematically inconsistent with observationally‐based (i.e., top‐down) diagnostic source apportionment of BC in East Asia based on the 14 C‐BC fingerprint (Andersson et al, ; Chen et al, ; Fang et al, ; Li et al, ; Liu, Mo, et al, ; Ni et al, ; Zhang et al, ). These 14 C‐based source apportionments of BC showed that fossil source is dominant in East Asian urban areas (e.g., Beijing, Shanghai, and Guangzhou) and ~50% in Himalayan‐Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%